Hollow tubular porous covalent organic framework (COF) nanostructures - Pachfule, Pradip; Kandmabeth, Sharath; Mallick, Arijit; Banerjee, Rahul (Chemical Communications, 2015)
Hollow and tubular TpPa-COF structures have been synthesized by template-assisted replication of nanometer sized ZnO-nanorods. The hollow structures composed of microporous TpPa shells have high periodicity, moderate porosity, chemical stability and capsule shaped morphology as revealed by X-ray diffraction, porosity measurements, and SEM and TEM analyses.